Magnetic resonance imaging findings of plantar venous thrombosis: a comparative study with Doppler ultrasound - Maruichi , Marcelo Damaso; Zorzenoni , Fernando Ometto; Guimaraes, Julio Brandao; M Link , Thomas; Gomes Ormond Filho , Alipio; de Souza Nery, Caio Augusto; Astolfi Caetano Nico , Marcelo (Journal of the Foot & Ankle, 2024)
Objective: Analyze magnetic resonance imaging (MRI) findings, demographics and clinical data in patients with plantar venous thrombosis (PVT). Methods: A retrospective study screening patients with PVT, diagnosed with color Doppler ultrasound, who also underwent MRI of the foot and ankle. In the post-contrast MRI sequences, the intravascular filling defect was analyzed, and in the non-contrast MRI sequences, the diameter of the foot vessels was analyzed, and perivascular edema was documented. MRI exams from a control group without PVT were also analyzed. Results: Sixty-one cases and 204 controls were included. The lateral plantar veins were the most frequent location in the foot with PVT (63.9%). In all post-contrast sequences, an intravascular filling was seen. In the case group, veins had a significantly greater diameter compared to controls (p < 0.05), and perivascular edema was observed in all cases (100%). A history of trauma/mechanical overload of the foot was documented in 83% of the patients (p < 0.001). Conclusion: Our results showed that the lateral plantar vein was the most frequent location of PVT. An intravascular filling defect on post-contrast MRI sequences was seen in all PVT cases. Compared to the control group, all vessels had a greater diameter in the case group, and perivascular edema was observed in all cases. Our results also suggest that a clinical history of trauma or mechanical overload (physical activities) in the foot and ankle may be one of the causal factors of this pathology. Level of evidence III; Therapeutic studies - investigating the results of treatment; Retrospective comparative study